Izboljšana razpoznava dušenja z uporabo zvezne valčne transformacije - Slavič, Janko (Strojniški vestnik, 2002)
A continuous wavelet transform (CWT) based on the Gabor wavelet function is used to identify the damping of a multi-degree-of-freedom system. The basic procedures are already known, especially the identification with a Morlet CWT. This paper enhances the already known procedures in the sense of reducing the edge- effect. This makes it possible to identify the damping of high-frequency modes. Three methods are shown: the reduced time spread of the wavelet function method, the equivalent window area method and the reflected window method. The procedures are demonstrated on signals acquired from the lateral vibration of a uniform beam. We were able to identify the damping up to the sixth natural frequency.
Keywords: sistemi dinamični; ugotavljanje dušenja; transformacija valčkov; postopki ugotavljanja; valčna transformacija; dušenje